Cloning, nucleotide sequence, and expression of a gene encoding an adhesin subunit protein of Helicobacter pylori. - Evans, D G (1993)
Gene hpaA, which codes for the receptor-binding subunit of the N-acetylneuraminyllactose-binding fibrillar hemagglutinin (NLBH) of Helicobacter pylori, was cloned and sequenced. The protein expressed by hpaA, designated HpaA, was identified as the adhesin subunit on the basis of its fetuin-binding activity and its reactivity with a polyclonal, monospecific rabbit serum prepared against NLBH purified from H. pylori. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis and Western blots (immunoblots) showed that the cloned adhesin has the same molecular weight (20,000) as that found on H. pylori. Also, HpaA contains a short sequence of amino acids (KRTIQK) which are all either identical or functionally similar to those which compose the sialic acid-binding motif of Escherichia coli SfaS, K99, and CFA/I. Affinity-purified antibody specific for a 12-residue synthetic peptide that included this sequence blocked the hemagglutinating activity of H. pylori and was shown by immuno-gold electron microscopy to react with almost transparent material on unstained H. pylori cells, which is consistent with previous observations concerning the location and morphology of the NLBH.